PENGUJIAN PECKING ORDER THEORY MENGGUNAKAN REGRESI DATA PANEL PADA INDUSTRI MAKANAN DAN MINUMAN - Yunika Murdayanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
The principal objective in this paper is to ascertain the extent to which Myers (1984) Pecking Order Theory (POT) of business financial appears to explain leverage amongst a pane! of 17 food and beverage companies, taken from Jakarta Stock Exchange during period 2003-2005. The analysis using Panel Data Regression and the research findings reported in the paperthat only profitability and growth significantly influence leverage using both OLS (Ordinary Least Square) and fixed effect. But with OLS, the result finding more significant than fixed effect and random effect. However, the findings also suggest the need for a modified POT that more fully reflects the spade cirazatances and nuances of food and beverage leverage especially when using between long term and short term debt. A full specification fora modified POTof leverage & food and beverage is proposed as a basis for further inquiry in the area.Keywords: pecking order theory, leverage, profitability, growth, size, age, asset